EVALUASI PENGALAMAN PENGGUNA APLIKASI MOBILE PERPUSTAKAAN DIGITAL IPUSNAS MENGGUNAKAN METODE UX HONEYCOMB - Aprilia, Nandita Ajeng; Faroqi, Asif; Mukaromah, Siti (Universitas Serang Raya, 2024)
The iPusnas application is a digital library platform developed by the National Library of the Republic of Indonesia to provide easy and free access to the Indonesian people. Based on data from Google Play Store in January 2024, iPusnas has been downloaded by more than 1 million users with an average satisfaction rating of 3.4 out of 5 points. Reviews on the Google Play Store show several problems, namely in the user experience, namely iPusnas users feel that the application features are inefficient and take a long time. Users also face difficulties while using the app on different devices and varying internet conditions. Apart from that, the interface is considered outdated, causing discomfort when using the application. This research aims to identify variables that influence the user experience of the iPusnas application based on the UX Honeycomb framework, which includes 7 indicators grouped into 3 variables: Think (useful, valuable, credible ), Feel (desirable, credible), and Use (findable, accessible, usable). The research results show that all variables and indicators significantly influence user experience. The Feel variable has the largest influence of 0.444, followed by Use of 0.346 and Think of 0.202. The results of this research can be used as consideration for developing recommendations for application improvements, especially in the user experience aspect, by considering the priority order of importance of the variables and indicators that have been analyzed.